Evapotranspiracion diaria del tomate determinada mediante un lisimetro de pesada - Rodriguez, R.=700 1 Pire, R.
(Es, En)
ilus., 5 ref.
Keywords: TECNOLOGIA; TOMATE; RIEGO; VENEZUELA; AGRONOMIA TROPICAL